2018
DOI: 10.14740/cr667w
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis and Treatment of Coronary Heart Disease in Asymptomatic Subjects With Advanced Vascular Atherosclerosis of the Carotid Artery (Type III and IV b Findings Using Ultrasound) and Risk Factors

Abstract: BackgroundA study was conducted as to whether the early diagnosis of coronary heart disease in asymptomatic subjects with advanced atherosclerosis of the carotid artery which additionally shows at least one risk factor is successful using ultrasound technology.MethodsWithin the scope of an occupational screening program using subjects from diverse employment sectors, people were given the opportunity to determine their risk of heart attack. During the study the total plaque area (TPA), the maximum plaque thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 29 publications
(13 reference statements)
1
32
0
2
Order By: Relevance
“…AS is considered the pathological basis for the occurrence and progression of coronary heart disease (16). miRNAs are a group of endogenous conserved non-coding small-molecule single-stranded RNAs that are widely distributed in eukaryotes and are involved in the regulation of gene expression at the post-transcription level (16). Previous studies have identified that the expression of miRNA is associated with the formation of atherosclerotic plaques (11,17).…”
Section: Discussionmentioning
confidence: 99%
“…AS is considered the pathological basis for the occurrence and progression of coronary heart disease (16). miRNAs are a group of endogenous conserved non-coding small-molecule single-stranded RNAs that are widely distributed in eukaryotes and are involved in the regulation of gene expression at the post-transcription level (16). Previous studies have identified that the expression of miRNA is associated with the formation of atherosclerotic plaques (11,17).…”
Section: Discussionmentioning
confidence: 99%
“…33 Similarly, asymptomatic subjects with advanced atherosclerosis of the carotid artery (carotid plaques with a CIMT $ 3.5 mm and flat carotid plaques with a CIMT > 2 mm) have been shown to have a high risk of coronary heart disease. 34 In the High Risk Plaque (HRP) Bioimage study, hazard ratios for major adverse cardiovascular events (MACE) for the maximum carotid plaque thickness were 1.96 (95% CI 0.91-4.25, p = 0.015) for primary MACE [cardiovascular death, myocardial infarction, or stroke] and 3.13 (95% CI 1.80-5.51, p < 0.001) for secondary MACE (all-cause death, MI, ischemic stroke, unstable angina, or coronary revascularization). 35 Advantages.…”
Section: Two-dimensional Techniques For Quantifying Plaquementioning
confidence: 99%
“…Therefore, an early detection of ischemic stroke and its prevention have important practical significance, which may ultimately lead to better health outcomes and reduce the financial burden inherent to diseases associated with a long-term disability. Carotid artery stenosis is closely related to ischemic stroke (Eckstein et al, 2013;Gupta et al, 2012;Lu & Wang, 2016) and is mainly caused by carotid atherosclerosis (Adams, Bojara, & Schunk, 2018;Liu et al, 2017) because of embolic sequelae as a consequence of underlying atherosclerosis which can incur/ cause secondary hemodynamic disturbances. The role of inflammation in the pathogenesis of carotid atherosclerosis has been well established (Borne et al, 2017;Casiglia & Tikhonoff, 2007), and the role of various inflammatory cells and mediators involved in carotid disease and stroke should be well investigated in order to better predict/ identify at-risk patients (Ammirati, Moroni, Norata, Magnoni, & Camici, 2015;Casiglia & Tikhonoff, 2007;Horne et al, 2005;Woollard & Geissmann, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Carotid artery stenosis is closely related to ischemic stroke (Eckstein et al, 2013;Gupta et al, 2012;Lu & Wang, 2016) and is mainly caused by carotid atherosclerosis (Adams, Bojara, & Schunk, 2018;Liu et al, 2017) because of embolic sequelae as a consequence of underlying atherosclerosis which can incur/ cause secondary hemodynamic disturbances. Carotid artery stenosis is closely related to ischemic stroke (Eckstein et al, 2013;Gupta et al, 2012;Lu & Wang, 2016) and is mainly caused by carotid atherosclerosis (Adams, Bojara, & Schunk, 2018;Liu et al, 2017) because of embolic sequelae as a consequence of underlying atherosclerosis which can incur/ cause secondary hemodynamic disturbances.…”
mentioning
confidence: 99%